Analysis of the Effect of Sharia Bank Financing and Investment on Economic Growth through Micro, Small and Medium Enterprises (MSMEs) Credit - Syamsuri, Helmy; Wahab, Abdul; Sumarlin, Abdul (Formosa Journal of Multidisciplinary Research, 2024)
This study seeks to examine the impact of sharia bank financing and investment on economic growth in Indonesia by analyzing lending to micro, small, and medium companies (MSMEs) utilizing time series data. This research characterizes economic growth through the Gross Regional Domestic Product (GRDP) for each province in Indonesia. This study utilizes secondary data from 2011 to 2022 sourced from BPS, OJK, and Bank Indonesia, analyzed using the Path Application. This report assesses the direct and indirect funding of Islamic banks and their involvement in economic growth via Micro, Small, and Medium Enterprises (MSME) credit. The research findings indicate that the Islamic bank funding variable does not significantly influence the MSME credit variable; nevertheless, the investment variable does have a substantial impact on the Micro, Small, and Medium Enterprises (MSME) credit variable.